Gamification Animation Video Modelled CIRC to Improve Reading Comprehension Skills on Narrative Discourse of Grade II Students - Irenewati, Inggit; Sukardi (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Teachers' use of learning media still needs to be improved, and learning models still need to be developed. Teachers at school only utilize books and simple pictures. This results in students' reading comprehension skills in narrative discourse in Indonesian language lessons needing to improve. This research aims to create a gamification animation video with a CIRC model to improve the reading comprehension skills of grade II elementary school students. The type of research used in this study is research and development (R&D), which uses the research model design from Borg and Gall. The subjects of this research were grade II students, as many as 25. The data collection methods used in this research are observation, interview, and questionnaire or questionnaire. The instrument used was a questionnaire sheet with a Likert scale. After the data was collected, it was analyzed using descriptive qualitative and quantitative data analysis methods. This study showed an increase in the average results before and after treatment in the small-scale and large-scale tests, so it can be concluded that the gamification of animated video media with the CIRC model can help improve students' reading comprehension skills in narrative discourse. This research is expected to help teachers enhance the quality of learning and help students have more creative and critical thinking potential.